PENINGKATAN KETERAMPILAN PROSES SAINS SISWA MTs MENGGUNAKAN MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATERI TEKANAN - Bima Prayoga Waskito; Martini Martini (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This research aims to describe the enhancement of students' science process skills with the application of guided inquiry model. The design used in the study was pre-experimental design with a research draft of one group pre-test post-test. Research was carried out with the subject of two classes VIII at MTs Hasyim Ash'ari Sukodono, where the first class had 32 students, and the second class had 36 students. This research was conducted in MTs Hasyim Asy'ari Sukodono because there has been no research in the school before, with the different time allocations from other schools, that is 4x35 minutes, where the curriculum determines the allocation of learning time 5x40 minutes and has not been established learning science process skills. Data collection techniques in the form of a question description that corresponds to the science process skills indicator. The result is the submission of science process skills, the percentage of achievement of each aspect of science process skills, n-gain pre-test and post-test, and n-gain every aspect of science process skill. The results showed that there has been an enhancement in every aspect of the science process skills, increasing the achievement percentage of each aspect of science process skills, and increasing the n-gain of each aspect of science process skills in two classes of 0.59 with medium category and 0.64 with medium category. Based on these results, it can be concluded that the guided inquiry model can enhance the students' science process skills, and can be applied to the pressure topic.